Feasibility of Student Worksheets based on Critical Thinking Skills on the Topic of Heat and Temperature - Yenny Warnida; Muhammad Zaini; Suyidno Suyidno (Jurnal Ilmiah Pendidikan Fisika, 2023)
In the industrial era 4.0, critical thinking is indispensable in dealing with various daily life problems. However, these skills are less practised in schools. Therefore, this study aims to produce feasible worksheets to train students' critical thinking skills on temperature and heat. Five worksheets are developed: solid expansion, liquid expansion, gas expansion, heat and Black's principle. The research design used Tessmer's formative evaluation, including self-evaluation, expert review, individual trials, small group trials, and field trials. The validity of the worksheet was obtained through assessment by three experts and two science learning practitioners. Individual tests on three students, small group tests on nine students, and field tests on 32 students. The results showed: (1) the worksheets are valid because the results of content and construct validation on the five worksheets are 91.88; 92.81; 93.44; 93.75; and 92.81 with very valid categories; and (2) the worksheets are feasible because the content, expected, and actual feasibility scores are 84.44; 87.62, and 86.41 respectively with very good categories. Thus, the worksheets are feasible to use in science learning. These worksheets can be an alternative for educators in increasing the activity of students to improve learning outcomes, especially critical thinking.